Executive retirement plan freezes and firm policies - Petrou, Zacharias; Vlittis, Adamos (My University, 2025)
When firms freeze their employees qualified defined benefit (DB) pension plans, they often re-evaluate and may similarly freeze their non-qualified supplemental executive retirement plans (SERPs). This study draws from agency theory to investigate the determinants and consequences of SERP freezes. We find that the decision to freeze SERPs is predominantly influenced by the power dynamics between top executives and the board of directors, alongside talent retention concerns. Moreover, our analysis reveals that SERP freezes lead to significant changes in corporate behavior. Firms that implement these freezes tend to distribute pension-related cost savings to their shareholders and are less likely to pursue diversification strategies than firms that keep their SERPs open. This risk-shifting behavior manifests in lower equity and higher credit risk post-freeze. Overall, this study provides insights into the determinants of SERP freezes and enhances our understanding of the incentive alignment function of SERPs' within top executives' compensation structures.
Keywords: Pension plan freezes; Supplemental executive retirement plans; Efficient contracting; Managerial power